The Relationship Between Internet Fraud and Psychoactive Substance Use Disorder: A Narrative Review - Falade, Joshua; Ajiboye, Oluwafemi Blessing; Eegunranti, Benjamin Adekunle; Ojo, Foluso Olamide (FUDMA Journal of Sciences, 2026)
Increase in internet fraud is a growing public health issue, particularly in relation to substance use disorders among youth and adolescents. Review explores the complex relationship between internet fraud and drug addiction, focusing on potential solutions to reduce addiction, particularly in young people. A comprehensive search was conducted between March and November 2023 across Google Scholar, PubMed, and the Cochrane Library to gather articles on internet fraud and drug addiction. The internet serves various roles, including cybercrime such as identity theft, online drug trafficking, and cyberstalking, which introduce unique risks. Addiction is influenced by neurobiological, psychological, and societal factors, with the brain’s reward system, genetics, environment, and peer pressure playing key roles. The relationship between internet fraud and addiction is bidirectional, where each worsens the other. The review emphasizes the need to raise awareness about the interconnected risks of internet fraud and drug abuse, particularly for youth.